2021
DOI: 10.3390/sports9100142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Training with Elastic Bands on Strength and Fatigue Indicators in Paralympic Powerlifting

Abstract: Background: Variable resistance training has recently become a component of strength and conditioning programs. Objective: This randomized counterbalanced cross-over study aimed to investigate the use of elastic bands (EB) and the traditional method (TRAD) and force indicators in a training session. Methods: 12 Paralympic athletes (age: 28.60 ± 7.60 years) participated in this three-week study. In the first week, the participants were familiarized with EB and TRAD and were tested for maximal repetition (1-RM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Thus, the evaluation of an athlete's training status and initial condition is the crucial point for the correct elaboration of a training program to be applied in different phases of the sports preparation [11]. In these initial conditions, some training variables are manipulated to prescribe and control resistance training programs such as: sets, time intervals, position and intensity [11][12][13]. On the other hand, in these initial conditions, there are possible disparities between different training methods to determine mechanical outputs in strengthpower exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the evaluation of an athlete's training status and initial condition is the crucial point for the correct elaboration of a training program to be applied in different phases of the sports preparation [11]. In these initial conditions, some training variables are manipulated to prescribe and control resistance training programs such as: sets, time intervals, position and intensity [11][12][13]. On the other hand, in these initial conditions, there are possible disparities between different training methods to determine mechanical outputs in strengthpower exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning training, the use of elastic bands (vs. the fixed-resistance methodology) in PP seems to promote overload, increase fatigue, and decrease strength, whilst it appears to be an effective and common practice in powerlifting [ 65 ]. However, this conclusion is drawn from one study only [ 28 ], warranting further research in the field. As well, the determinants of training in terms of the optimal preparation interval should be further investigated: the only study available [ 29 ] failed to detect any age-, sex-, and gender-specific differences.…”
Section: Discussionmentioning
confidence: 88%
“…Seven studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] were excluded with reason ( n = 2, not reporting sufficient details; n = 5, not disaggregating data according to para-sports discipline). Finally, 37 studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] were retained in the present scoping review. We found that the included studies focused on a range of aspects involving health, classification, the etiology of injuries, and performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate-to-high correlations were found among most performances, as well as correlation between body fat percentage and both CMJ and Yo-Yo IR1 results in addition to CMJ's highest correlation with TS. [5]. Compared with traditional strength training, authors did not find any differences in force indicators but (higher) fatigue and (longer) time to reach maximum isometric force.…”
mentioning
confidence: 84%